Xenotransplantation of European Eel (Anguilla anguilla) Spermatogonia in Zebrafish (Danio rerio) and European Sea Bass (Dicentrarchus labrax) - Marta Blanes-García; Zoran Marinović; Marina Morini; Alain Vergnet; Ákos Horváth; Juan F. Asturiano (Fishes, 2024)
The European eel encounters challenges in achieving sexual maturation in captivity, which has been a concern for researchers. This study explores surrogate broodstock technology as an alternative approach for eel production. The present study aimed to evaluate zebrafish and European sea bass as potential recipients for European eel spermatogonia transplantation, given the abundance of eel type A spermatogonia (SPGA). Immature European eel testes were dissected and maintained at 4 °C or cryopreserved. SPGA were obtained by dissociation of fresh or post-thawed tissue, employing an enzymatic solution, and then labelled with fluorescent membrane marker PKH26. SPGA from fresh tissue were transplanted into wild-type zebrafish larvae and triploid European sea bass larvae, while SPGA from cryopreserved testis were transplanted into vasa::egfp transgenic zebrafish larvae. One-and-a-half months post-transplantation (mpt), fluorescent donor cells were not detected in the gonads of zebrafish or European sea bass. Molecular qPCR analyses at 1.5 or 6 mpt did not reveal European eel-specific gene expression in the gonads of any transplanted fish. The findings suggest that the gonadal microenvironments of zebrafish and European sea bass are unsuitable for the development of European eel spermatogonia, highlighting distinctive spermatogonial stem cell migration mechanisms within teleost species